Influence of Bariatric Surgery on the Expression of Nesfatin-1 in Rats with Type 2 Diabetes Mellitus - Xia, Zefeng; Wang, Geng; Li, Huiqing; Hu, Chaojie; Wang, Qingbo; Li, Anshu; Zhao, Ende; Shuai, Xiaoming; Wang, Jiliang; Cai, Kailin; Tao, Kaixiong; Wang, Guobin (Current Pharmaceutical Design, 2015)
Objective: Bariatric surgery has been reported to be very effective in the remission of type 2 diabetes mellitus (T2DM). However, the mechanism is still under debate. Nesfatin-1, a recently discovered anorexigenic neuropeptide, was reported to be very important in glucose metabolism and regulating food intake. In this study, the effects of bariatric surgery on the expression and regulation of nesfatin-1 were discussed. Methods: T2DM was induced in SD rats by a diet high in sugar and fat plus a low dose of streptozotocin (STZ) (25 mg/kg) injection. Bariatric surgeries, including Roux-En-Y Gastric Bypass (RYGB) and sleeve gastrectomy (SG), were performed on these rats. Two months after the surgery, the plasma nesfatin-1 level and the expression of nesfatin-1 in different organs of the rats were tested. Next, in vivo administration of nesfatin-1 after surgery was performed to investigate the role of nesfatin-1 in bariatric surgery. Results: Both RYGB and SG could reduce the weight of the rats. However, only RYGB had significant effects on the blood glucose level. Neither surgeries seemed to affect the blood concentration of insulin. However, RYGB significantly improved insulin sensitivity. Expression of nesfatin-1 in the plasma and relative organs decreased in T2DM rats and rose again after RYGB; however, this pattern did not occur in SG. Injection of nesfatin-1 after SG significantly improved insulin resistance and reduced blood glucose levels. Conclusions: Nesfatin-1 may improve insulin sensitivity in T2DM rats and thus plays a very important role in the remission of T2DM after RYGB. This neuropeptide could be a new target for directing future improvements in the bariatric surgical process.
Keywords: bariatric surgery